2019
DOI: 10.1002/mgg3.815
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel splice site mutation in the SERAC1 gene responsible for the MEGDHEL syndrome

Abstract: Background MEGDHEL is an autosomal recessive syndrome defined as 3‐MEthylGlutaconic aciduria (3‐MGA) with Deafness, Hepatopathy, Encephalopathy, and Leigh‐like syndrome on magnetic resonance imaging, due to mutations in the SERAC1 (Serine Active Site Containing 1) gene, which plays a role in the mitochondrial cardiolipin metabolism. Methods We report the case of a young patient who presented with a convulsive encephalopathy, 3‐methylglutaconic aciduria, deafness, and bilateral T2 hypersignals of the putamen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Figure 2 illustrates the mutations identified in this case in the context of the SERAC1 gene and protein with its domains. Mutations previously reported in the literature are also marked (Ling et al, 2021;Maas et al, 2017;Roeben et al, 2018;Sarig et al, 2013;Snanoudj et al, 2019). The reported pathogenic mutations span the spectrum from frameshift, nonsense, missense, splice site, extension, and deletion variants.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Figure 2 illustrates the mutations identified in this case in the context of the SERAC1 gene and protein with its domains. Mutations previously reported in the literature are also marked (Ling et al, 2021;Maas et al, 2017;Roeben et al, 2018;Sarig et al, 2013;Snanoudj et al, 2019). The reported pathogenic mutations span the spectrum from frameshift, nonsense, missense, splice site, extension, and deletion variants.…”
Section: Discussionmentioning
confidence: 90%
“…The intragenic deletion of exons 2-4 identified in this patient includes the start codon and thus is predicted to result in decreased expression of normal protein; whether that results from complete absence of expression, production of a truncated protein, or nonsense-mediated decay can only be confirmed with additional expression studies. Moreover, as the deletion involves the transmembrane domain, a variant protein if synthesized using an alternative initiation codon, may not localize to the speculated intracellular location et al, 2021;Maas et al, 2017;Roeben et al, 2018;Sarig et al, 2013;Snanoudj et al, 2019; NCBI reference sequence: NM_032861.4; NP_116250)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified a causal relationship between SERAC1 variants and MEGDEL syndrome (11)(12)(13)(14)(15). Approximately 70 cases of MEGDEL syndrome have been reported worldwide according to a report in 2020 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal function can increase the ratio of phosphatidylglycerol-34:1 to phosphatidylglycerol-36:1 and decrease the level of mono-acyl-glycerol (bis) phosphate and subsequently altering the accumulation of cholesterol ( Wortmann et al, 2012 ). Recently, SERAC1 pathological variants were also found to change acyl-chain composition of PG, a precursor of cardiolipin, giving rise to normal levels of cardiolipin but possessing altered acyl chain composition ( Snanoudj et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%